Evaluation and Injection Parameter Optimization for Polymer Flooding with Different Kinds of Profile Control Agents. (3rd September 2013) - Liu, Yikun; Deng, Qingjun; Chen, Gang; Liang, Shuang; Chen, Lingyun
Abstract : Injecting profile control agent (PCA) into deep reservoir can decrease the inefficient circulation of injected water effectively, which is critical to improve polymer flooding in heterogeneous reservoir. Polymer flooding contrast experiments were carried out with three PCAs, respectively; the influence of different injection times on recovery is analyzed, and the best injection rate of PCA is determined. The result shows that the effect of compound ion PCA, anionic delay-action cross-linking PCA, and luminum citrate cross-linking PCA gets worse in turn. The effect of injecting PCA before polymer flooding is better than that of injecting it during and after the procedure. As the PCA rate increases, the recovery increment raises, but the increasing ranges decrease. The best rate of PCA is 0.10PV, considering technical and economic effects.